A MnO2 nanosheet/single-wall carbon nanotube hybrid fiber for wearable solid-state supercapacitors. (December 2018) - Li, Guo-Xian; Hou, Peng-Xiang; Luan, Jian; Li, Jin-Cheng; Li, Xin; Wang, Han; Shi, Chao; Liu, Chang; Cheng, Hui-Ming
Abstract: Carbon nanotubes based fiber supercapacitor is considered as one of the most promising power sources for wearable electronic devices because of their remarkable mechanical and electrical properties. However, how to obtain flexible and highly conductive fibers with a high active material loading to give the supercapacitor high energy and power densities remains a great challenge. Here, we report a highly conductive hybrid fiber consisting of single-wall carbon nanotubes and ultrathin MnO2 nanosheets prepared by a scalable wet-spinning method. The mass percentage of active MnO2 in the hybrid fiber is as high as 75% and the intimate contact between the MnO2 sheets and the single-wall carbon nanotubes provides highly conductive pathways, while the abundant pores in the material enable fast ion transport. As a result, a flexible solid-state supercapacitor assembled from the hybrid fiber exhibits a very high volumetric capacitance of 74.8 F cm −3, an energy density of 10.4 mWh cm −3, and good cycling stability. This all-solid-state fiber supercapacitors with excellent flexibility are also woven into a textile demonstrating its ability of lighting wearable electronics. Graphical abstract: Image 1